Identification runoff source area in Tropical watershed - Heshmatpoor, Ali; Sulaiman, Wan Nor Azmin; Zakaria, Mohamad Pauzi; Idris, Azni (2009)
Models are needed to describe how nonpoint source area of a watershed affect the rainfall-runoff process in tropical region, yet little spatially distributed data exist to develop such models. Hence, a coupled GIS-event base storm runoff model in a variable source area is developed. The model use grid-formatted map data supported by the Geographical Information System (GIS) and generates distributed results for runoff depth, discharge and coefficient of saturated area fraction. The GIS grid-based distributed CN-VSA method was evaluated for two (W1= 2.29 Km2 , W2 = 0.88 Km2 ) small watersheds located in tropical region in Malaysia. The average Nash-Sutcliffe (1970) efficiency for predicting saturated area fraction and runoff within and outlet of the watershed (W1) using verification between observed and model simulated data for fifteen storm events were (R2 =0.99) and (R2 =0.86), respectively. Coefficients indicated a good efficiency for model prediction. Since, the model proposed was found to be suitable for prediction of saturated area fraction (Af) and sources area of runoff, the proposed model was applied for unmonitored sub-watersheds W11, W12, W13 (of watershed W1) and watershed W2, respectively.